A naturalistic inquiry into the attitudes toward mathematics and mathematics self-efficacy beliefs of middle school students - Stramel, Janet K. (Kansas State University, 2010)
While there has been much quantitative research done in the area of attitudes and self-efficacy beliefs, this study sought hear the voices of the middle school child. Therefore, this qualitative study investigated the attitudes toward mathematics and mathematics self-efficacy beliefs of middle school students in one middle school in western Kansas. The conceptual framework for this study is supported by the research of Albert Bandura on Social Cognitive Theory. This study used a naturalistic inquiry approach and data were collected from multiple sources, including short-answer questionnaires, classroom observations, and one-on-one interviews. Coded data were examined for patterns, themes, and relationships. Middle school students in this study exhibited positive, negative, and variable attitudes toward mathematics, and both positive and negative mathematics self-efficacy beliefs. Students attribute their high mathematics self-efficacy beliefs to the teacher or the high grades they receive on daily assignments, as well as the scores they receive on state and local assessments. Conversely, middle school students have low mathematics self-efficacy beliefs when they feel unsuccessful or distressed, and they attribute those beliefs to the low grades they receive on daily assignments and assessments, as well as the distress of not understanding the mathematics. Middle school students told their mathematical stories of the change in attitudes toward mathematics and mathematics self-efficacy beliefs, and attributed positive changes to the mathematics teacher. Negative changes in attitudes toward mathematics and mathematics self-efficacy beliefs were attributed to the amount of homework expected at the middle school level, as well as the lack of hands-on activities. The influence of the teacher, grades, and hands-on activities impact middle school students’ attitudes toward mathematics and mathematics self-efficacy beliefs. There is a relationship between attitudes toward mathematics and mathematics self-efficacy beliefs. Low mathematics self-efficacy beliefs and poor attitudes toward mathematics are related since low mathematics self-efficacy beliefs and poor attitudes toward mathematics are highly connected. Conversely, high mathematics self-efficacy beliefs and good attitudes toward mathematics are highly related. Middle school students’ experiences impact both mathematics self-efficacy beliefs and attitudes toward mathematics. Students’ mathematics self-efficacy beliefs impact their attitudes toward mathematics.
Keywords: Middle school education; Mathematics education; Attitudes toward mathematics; Mathematics self-efficacy beliefs; Naturalistic inquiry; Qualitative; Education, Curriculum and Instruction (0727); Education, Mathematics (0280)